Persistent Systemic Microbial Translocation and Intestinal Damage During Coronavirus Disease-19 - Oliva, Alessandra; Miele, Maria Claudia; Di Timoteo, Federica; De Angelis, Massimiliano; Mauro, Vera; Aronica, Raissa; Al Ismail, Dania; Ceccarelli, Giancarlo; Pinacchio, Claudia; d’Ettorre, Gabriella; Mascellino, Maria Teresa; Mastroianni, Claudio M. (Frontiers in Immunology, 2021)
Microbial translocation (MT) and intestinal damage (ID) are poorly explored in COVID-19. Aims were to assess whether alteration of gut permeability and cell integrity characterize COVID-19 patients, whether it is more pronounced in severe infections and whether it influences the development of subsequent bloodstream infection (BSI). Furthermore, we looked at the potential predictive role of TM and ID markers on Intensive Care Unit (ICU) admission and in-hospital mortality. Over March–July 2020, 45 COVID-19 patients were enrolled. Markers of MT [LPB (Lipopolysacharide Binding Protein) and EndoCab IgM] and ID [I-FABP (Intestinal Fatty Acid Binding Protein)] were evaluated at COVID-19 diagnosis and after 7 days. As a control group, age- and gender-matched healthy donors (HDs) enrolled during the same study period were included. Median age was 66 (56-71) years. Twenty-one (46.6%) were admitted to ICU and mortality was 22% (10/45). Compared to HD, a high degree of MT and ID was observed. ICU patients had higher levels of MT, but not of ID, than non-ICU ones. Likewise, patients with BSI had lower EndoCab IgM than non-BSI. Interestingly, patients with high degree of MT and low ID were likely to be admitted to ICU (AUC 0.822). Patients with COVID-19 exhibited high level of MT, especially subjects admitted to ICU. COVID-19 is associated with gut permeability.